Generalized adequate rings - Zabavskii, B. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We introduce a new class of rings of elementary divisors which generalize adequate rings. We show that the problem of whether every commutative Bezout domain is a domain of elementary divisors reduces to the case where the domain contains only trivial adequate elements (namely, the identities of the domain).